AVALIAÇÃO DO COMPORTAMENTO MECÂNICO DO POLIÉSTER ORTOFTÁLICO RETICULADO COM ADIÇÃO DE PET RECICLADO - Gonçalves, Sandra Cunha; Fornari, Celso Carlino (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704794 One of the major problems faced by modern society is to find a suitable disposal for excess solidwaste generated, particularly disposable products. In this context, the use of recycled PET asreinforcement in composites, is an idea that arises in order to seek alternatives for the recycling ofthis waste. We studied the influence of the variation in the mechanical properties of PET fiberreinforced polyester. Test specimens were made of pure matrix and 5 to 10% of PET in the particlesize of 40, 60 and 80 mesh. We evaluated the mechanical behavior of composites by means ofbending tests on three points. The results showed a gradual increase in modulus with increasingpercentage of PET in smaller particle sizes, resulting in significantly reducing deformation inrelation to the matrix.